The Effect of Surface Modification on Mechanical and Thermal Properties of Bamboo Fiber Polymer Composite: A Systematic Literature Review (SLR) - Abd Talib, Nur Idayu; Ahmad, Mazatusziha; Roslan, Mohd Nazrul (Progress in Engineering Application and Technology, 2022)
Bamboo fiber polymer composite was expanded as an environmentally friendly materials that are biodegradable and can replace use of synthetic polymer. The main objective of this study was to identify the modified bamboo fiber and fiber content used as reinforcement in various type of polymer matrices, focusing on the effect of thermal and mechanical properties. Selection of study through PRISMA method, finalized twenty-eight studies to be used for systematic literature review (SLR). The quality of selected articles was evaluated in order to come out with data related to the objectives of the study by correlate the surface modification and fiber content on the performance of bamboo fiber polymer composite. Two sub-group were highlighted in this study; the performance of mechanical properties such as tensile and flexural strength and thermal properties such as thermal decomposition and glass transition of bamboo fiber polymer composite was compared to untreated bamboo fiber. In addition, the fiber content was identified in range 30wt%-40wt% to boost the performance between fiber and polymer matrices. Thus, in this study, the systematic literature review provided comprehensive information and act as reference on the determination of the range of fiber content and effect of surface modification on bamboo fiber polymer composite.